TRANSFORMASI KONFLIK AGAMA DAN STRATEGI REFORMATIF PADA PEMBANGUNAN BUDAYA DAMAI - Abd. Aziz Faiz (Jurnal Sosiologi Agama, 2020)
Conflict accompanies religious life in Indonesia. Social interactions based on prejudice and stereotype still thrive in social relations. On the other hand, for some people religion is seen as a pathological source of conflict, not as a potential creativity for the building of a peaceful culture. In that context, this paper is compiled through a descriptive qualitative method with literature study. This method is used to discover key concepts and their application to efforts to find transformation and reformative strategies from religious conflicts. This transformation and reformative strategy is placed on the assumption that each culture has independent media to build a culture of peace through the internal culture of the community as an effective reconciliation force in building relationships between religious schools (mazhab) and social groups. From this analysis, three main concepts and strategies are found for the development of a culture of peace; first, opening the faucet of intercultural communication based on the existing culture in society, second, building a reformative-transformative national culture that is relevant to the needs of society and the current development. Third, the reformulation of religious understanding and interpretation as the spearhead of religious peace building. These three things have significance for efforts to build a basis for making every policy, social transformation and development of a peaceful culture to achieve future harmony for socio-religious life in Indonesia.